2007
DOI: 10.1080/1612197x.2007.9671818
|View full text |Cite
|
Sign up to set email alerts
|

Effects of motor imagery training on service return accuracy in tennis: The role of imagery ability

Abstract: International audienceThis study examined how imagery ability could affect motor improvement following motor imagery training in tennis. Skilled tennis players were divided into 3 groups with regard to their MIQ scores (good imager, poor imager and control group). During a pre-test, participants physically performed 15 service returns towards a target. The motor imagery training period was included during physical training for 15 sessions and each session consisted of 2 series of 15 imagined trials and 15 phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
107
1
11

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(128 citation statements)
references
References 35 publications
9
107
1
11
Order By: Relevance
“…Goss et al (1986) provided an early indication that those with better imagery ability benefit more from imagery use than those with poorer imagery ability. This finding has been supported by more recent studies such as Robin et al (2007), in which better imagers experienced greater improvements in tennis serve return accuracy following an imagery intervention compared to those with lower imagery ability.…”
Section: Introductionsupporting
confidence: 58%
“…Goss et al (1986) provided an early indication that those with better imagery ability benefit more from imagery use than those with poorer imagery ability. This finding has been supported by more recent studies such as Robin et al (2007), in which better imagers experienced greater improvements in tennis serve return accuracy following an imagery intervention compared to those with lower imagery ability.…”
Section: Introductionsupporting
confidence: 58%
“…We decided to remove the vividness rating and retain ease of imaging for two reasons. Firstly, this dimension has been used extensively in other questionnaires (e.g., MIQ-R, MIAMS), and has been shown to influence the effectiveness of imagery interventions (e.g., Robin et al, 2007), and moderate the relationship between imagery use and a range of outcomes (e.g., Goss et al, 1986;Cumming, 2008). Secondly, some athletes voiced difficulties in comprehending what was meant by the vividness of an image.…”
Section: Resultsmentioning
confidence: 99%
“…The effectiveness of an imagery intervention increases for those reporting a higher ability to image (Hall, Buckolz, & Fishburne, 1992). For example, Robin et al (2007) demonstrated that individuals with higher imagery ability experienced greater improvement in the accuracy of their tennis serve return compared with poorer imagers. In addition, Martin et al (1999) hypothesized imagery ability would moderate the relationship between imagery use and its intended outcome-a proposal that has received support (Goss, Hall, Buckolz, & Fishburne, 1986;Cumming, 2008).…”
mentioning
confidence: 99%
“…Although imagery can be a beneficial technique for improving sport performance, its efficacy is influenced by the ease with which athletes can create and control images of their own performance (Martin, Moritz, & Hall, 1999;Weinberg, 2008). Indeed, researchers (e.g., Hall, Buckolz, & Fishburne, 1992;Robin et al, 2007) have implied that the imagery ability characteristics of the athlete are probably the most important factors that influence the effectiveness of imagery interventions. For example, Robin et al (2007) reported that whereas imagery was generally an effective technique for improving tennis serve return accuracy, the effectiveness of the intervention was meditated by the ease with which participants could perform imagery.…”
Section: Action Observation and Imagery Trainingmentioning
confidence: 99%
“…Indeed, researchers (e.g., Hall, Buckolz, & Fishburne, 1992;Robin et al, 2007) have implied that the imagery ability characteristics of the athlete are probably the most important factors that influence the effectiveness of imagery interventions. For example, Robin et al (2007) reported that whereas imagery was generally an effective technique for improving tennis serve return accuracy, the effectiveness of the intervention was meditated by the ease with which participants could perform imagery. In this experiment, those classified as good imagers based on their responses to the Movement Imagery Questionnaire, which measures ease of imagery generation, improved their service return performance to a greater extent than those classified as poor imagers.…”
Section: Action Observation and Imagery Trainingmentioning
confidence: 99%